A conciliação ambiental e o atendimento ambiental no estado de São Paulo - Zanquim Junior, José Wamberto (Universidade Federal de São Carlos, 2016)
The environment, a diffuse and common use right, requires the adoption of swift and effective solution to the existing conflicts and also the prevention of new occurrences. In this sense the traditional judicial resources present in Brazil with the task of solving the environmental demands, due to several factors, such as bureaucratization, absence of equipment, staff and specialization, and decisions, often late, lead to shortfalls, imposing the search for new ways and new directions. In this scope, glimpsing at an alternative to judicialization of environmental issues, the State of São Paulo, by means of Decree No. 60.342/2014 and the resolutions number 51 and number 48, both from the year 2014, issued by the State Department of environment, as well as, by Ordinance No. 18/2014 of coordination of Environmental Supervision, created the State administrative procedure nominated “Atendimento Ambiental e o Programa de Conciliação Ambiental” (“Environmental Care and Environmental Conciliation Program”), to apply penalties to environmental violations provided for in Federal Decree No. 6.514/2008. This procedure aims at the conciliatory solution of conflicts through limited mutual concessions on the percentages of discounts and suspension of the penalty values applied or their conversion into environmental services, due to the unavailable nature of environmental goods, and on deadlines for actions implementation and measures for the recovery of the affected areas. In this sense, the discounts are possible before proof of weakened economic situation, low schooling, commitment to recovery of damages, first offender status and contribution to the procedure. Furthermore, in addition to its conciliatory objective, the administrative procedure is intended to promote environmental education through providing environmental instructions set out in the booklet “Conduta Ambiental Legal” ("Cool Environmental Conduct"), reduce environmental liabilities, and remedy environmental damage. Also, the procedure seeks to add speed and efficiency in investigation and penalize environmental offenders while still in administrative level.
Keywords: Conflitos ambientais; Soluções alternativas; Concessões mútuas limitadas; Environmental conflict; Alternatives solutions; Limited mutual concessions; OUTROS::CIENCIAS